Computational Design of Immunogenic Nucleocapsid Peptides as Potential Vaccine Target Against Thailand Orthohantavirus - Saxena, Prakhar Vaidant (My University, 2023)
Thailand Orthohantavirus of the Hantaviridae Family is an emerging zoonotic virus and is responsible for causing hemorrhagic fever with renal syndrome and cardiopulmonary syndrome in humans. Therefore, a potential vaccine candidate is important due to the absence of any alternative viable treatments or vaccinations. Current study comprises of various immunoinformatic methods that were implemented to design a multi- peptide vaccine candidate against Thailand Orthohantavirus. Computational analysis was performed by using NetMHCIpan server 4.0 and NetMHCIIpan sever 4.1 to predict CD8+ T cell and CD4+ T cell epitopes, respectively. The required screening for allergenicity and antigenicity was performed using AllerTOP and Vaxijen severs, respectively. Multiple T and B cell epitopes were identified in four peptide fragments using different prediction tools. Molecular docking (HPEPDOCK sever) of HLA epitopes (ten for each class I and class II) reveal good binding interaction between the epitopes and HLA molecules. An assessment of the prevalence of identified peptides across six continents (Asia, Europe, Africa, Australia, North America and South America) was done using IEDB population coverage analysis. Therefore, these immunoinformatic analysis shows that these peptides can be used as a potential vaccines candidates for Thailand Orthohantavirus.
Keywords: Hantaviridae; Immunoinformatics; HPEPDOCK Server; Population Coverage